The transfer knowledge for the development of clinical guidelines informed on evidences - Carmona Clavijo, Gloria (2018)
This article shares the experience of the technology transfer (TT) developed by the Peruvian National Institute of Health (INS) towards the multidisciplinary clinical groups of different IPRESS and managers of the Ministry of Health (MINSA), inside the framework of the development of guidelines for Clinical Practice-Informed in Evidence (GPC-IE). It presents the evolutionary context of the CPG together with the role assumed by the INS, in their development of current regulations and in their implementation. It expresses the inherent situation to operationalization of the process that were not initially contemplated in the guideline and the contributions made to afford it; as the variability of the prioritization strategies of topics to be developed, the additional characteristics of the development group (GE) and methodology group (GM), the relevance of the management group, the pedagogical strategies used for the management of the clinical groups, the additional precisions that were carried out in relation to the declaration of conflict of interest (DCI) in order to contribute to transparency, and to strengthen the assumed TT. It shows the strategies used to assess the perspectives and preferences of patients. Finally it expresses the results and the challenges in the continuous TT in the framework of GPC-IE.